Proposal of Load Rejection Scheme Due to Minimum voltage in the Moyobamba – Tarapoto System at 138 Kv: https://doi.org/10.15332/24222399.2934 (Revista Cientifica Ingenio Magno, 2024)
The research begins with the objective of mitigating supply interruptions in the Cajamarca Norte – Caclic – Belaunde Terry – Moyobamba – Tarapoto – Juanji – Tochache – Aucayacu – Tingo María transmission system, through a proposal for an automatic load rejection scheme based on the detection of minimum voltage levels, and through the selective disconnection of specific loads in the system. To obtain the proposal for the automatic load rejection scheme, initially an exploration of the theoretical concepts involved in our research was carried out, to then collect the required information to help update the analyzed electrical system and validate our proposed results. After obtaining the results of various scenarios, it was possible to determine the optimal percentage for automatic load rejection in the studied system. Which allowed us to clearly observe the impact of the reset of the voltage values after the automatic load rejections were carried out. At the conclusion of the investigation, it was determined that the Belaunde Terry, Moyobamba, Tarapoto and Bellavista substations are the most sensitive to variations in electrical voltage, which makes them more susceptible to reaching the point of collapse with minimum levels of voltage. Based on this observation, it is suggested to include the participation of the loads of these substations in the load rejection scheme when the voltage reaches critical levels.
Keywords: Minimun voltage; load reject; unforeseen failures